Symbiotic Performances of Three Mesorhizobium huakuii Strains Inoculated to Chinese Milk Vetch Varieties - Liu, Fang; Yi, Mingxuan; Liu, Xinbao; Shen, Yixin; Li, Jianlong; Wang, Hui; Yang, Dianlin; Sun, Zhengguo (Frontiers in Plant Science, 2020)
Abstract：In this experiment, 4 varieties of Chinese milk vetch (Xinyang, Minzi No.6, Minzi 8487711, and Shishou) were used as host plants and inoculated with 3 strains of rhizobium (CCBAU 2609, M. h 93, and 7653R). The differences in their morphology, yield, and nodule characteristics at different growth stages were studied and the reasons for these differences were analyzed to explore the exclusivity between different varieties of Chinese milk vetch and strains of rhizobium. Results showed no significant difference in plant height and whole-plant dry weight at seedling stage under different treatments but significant differences in these characteristics at full flowering stage. The results indicated that Minzi 8487711 and Shishou were significantly better than the other varieties. During the whole growth period, the growth indexes and nodule characteristics of the 4 varieties inoculated with strain 7653R were better than those of the varieties inoculated with other strains. At full flowering stage, compared with that of the control group, the biomasses of Xinyang, Minzi No.6, Minzi 8487711, and Shishou had increased by 2.04-, 2.84-, 1.56-, and 2.69-fold, respectively, and nitrogenase activities increased by 3.82%, 9.60%, 6.21%, and 15.18%, respectively. Significant differences in the exclusivity between varieties and strains were observed. Minzi No.6–7653R and Shishou variety–7653R had the strongest exclusivity. The results showed that 7653R was a broad-spectrum and high-efficiency rhizobium strain. 7653R is recommended to be used in combination with Chinese milk vetch varieties, such as Minzi 8487711 and Shishou, to obtain advantages in yield and nitrogen fixation in production.